2005
DOI: 10.1007/s11274-005-0081-2
|View full text |Cite
|
Sign up to set email alerts
|

Physical Factors and Reuse Affect the Production of Cholesterol Oxidase in Reactors Containing Calcium Alginate-Immobilized Rhodococcus equi No. 23

Abstract: Some physical factors including initial pH of medium, cultivation temperature and shaking speed as well as reuse affecting the production of cholesterol oxidase (CholOx) in reactors containing calcium alginate-immobilized cells of Rhodococcus equi No. 23 were investigated. Results revealed that the free cells showed the maximum CholOx in the culture with an initial pH of 5.0, while culture inoculated with immobilized cells exhibited a broad pH range, 6.0-9.0, for maximum CholOx production. The immobilized and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In comparison with other microbial hydrolases, the production times of chitinases were long due to insoluble nature of the chitinous substrate, which reduced the number of batches. Furthermore, the presence of phosphate or calcium chelating agents could bind strongly with alginate and solubilize the bound Ca 2þ (16). To overcome …”
Section: Resultsmentioning
confidence: 99%
“…In comparison with other microbial hydrolases, the production times of chitinases were long due to insoluble nature of the chitinous substrate, which reduced the number of batches. Furthermore, the presence of phosphate or calcium chelating agents could bind strongly with alginate and solubilize the bound Ca 2þ (16). To overcome …”
Section: Resultsmentioning
confidence: 99%
“…Chang et al . observed that maximum COD was produced at 250 rpm from calcium alginate immobilized cells of R. equi .…”
Section: Discussionmentioning
confidence: 98%
“…Chang et al . investigated COD production by the immobilized cells of R. equi in Ca‐alginate beads and found that immobilized cells give maximum production at higher pH range (6.0–9.0) and temperature (30 °C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation